Sosialisasi dan Pendampingan Strategi Peningkatan Usaha Mikro Kecil dan Menengah (UMKM) di Desa Biring Ere (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This Community Service Program (PKM) aims to provide direct socialization and mentoring to Micro, Small, and Medium Enterprise (MSME) actors in Biring Ere Village to enhance the quality and sustainability of their businesses. MSMEs play a vital role in the village economy as drivers of local economic growth and employment. However, various obstacles such as limited access to capital, low quality of human resources, restricted market access, lack of product innovation, and weak business management remain major barriers. This community service activity was conducted through interactive socialization methods, skills training, direct mentoring, and focused group discussions involving MSME actors, village heads, village officials, and the general community. The materials presented included business development strategies, basic financial management, product marketing techniques, product innovation and diversification, and access to capital. The results demonstrated increased understanding among MSME actors regarding business development strategies, heightened motivation to innovate, formation of collaborative business groups, and enhanced awareness of the importance of sound business management. This program has had a significant impact on empowering the community's economy and strengthening the capacity of MSME actors in Biring Ere Village to face global economic challenges.